Pelaksanaan Dispensasi Kawin Bagi Anak Yang Masih Di Bawah Umur Di Pengadilan Agama Pariaman Kelas 1B (Studi Putusan Nomor 3/Pdt.P/2022/Pa.Prm) - Chiara Amelia; Helfira Citra; Rianda Prima Putri (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
In writing this thesis, the author discusses the problem of implementing a marriage dispensation at the Pariaman Class IB Religious Court. This is motivated by the existence of a marriage dispensation application at the Pariaman Religious Court Class 1B which invites questions about how the legal arrangements for marriage dispensation at the Pariaman Class 1B Religious Court and the basis for judges' considerations in granting the marriage dispensation application at the Pariaman Class 1B Religious Court. As for the writing method that the author uses, namely, qualitative data analysis, in which the author uses qualitative descriptive as well as document studies of the data in the Pariaman Religious Court Class 1B and interviews with the Pariaman Class 1B Religious Court judges as well as applicants who apply for a marriage dispensation. The results of this study indicate that the legal regulation of marriage dispensation is regulated in Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974, Regulation of the Supreme Court Number 5 of 2019 concerning Guidelines for Adjudicating Applications for Marriage Dispensation and the Compilation of Islamic Law. The judge's consideration in granting a marriage dispensation case is due to urgent reasons such as pregnancy out of wedlock, an already intimate relationship. The Religious Courts provide a marriage dispensation for the benefit of human life not only referring to the law but also based on the benefit of mursalah in order to avoid actions that are prohibited by customary and religious norms. It is recommended that parents pay more attention to their children's association so that undesirable things do not happen and that the judges of the Religious Courts in considering the application for a marriage dispensation must be more selective to reduce the occurrence of underage marriages even though the law has regulated the granting of marriage dispensations.